2014
DOI: 10.1002/bmc.3143
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective analysis of flecainide enantiomers using reversed‐phase liquid chromatography for assessing CYP2D6 activity

Abstract: Stereoselective analyses of flecainide enantiomers were performed using reversed-phase high-performance liquid chromatography (HPLC) equipped with a polysaccharide-based chiral column (Chiralpak AS-RH) and fluorescence detector. Excitation and emission wavelengths were set at 300 and 370 nm, respectively. Flecainide enantiomers in serum and urine were extracted using diethyl ether. The mobile phase solution, comprising 0.1 m potassium hexafluorophosphate and acetonitrile (65:35, v/v), was pumped at a flow rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This type of binding results in up to twofold variations in free drugs in the plasma and the volume of distribution between the enantiomers. [29][30][31][32][33] For instance, many antiarrhythmic medicines that include disopyramide, encainide, flecainide, mexiletine, propafenone, and tocainide are marketed as racemates. The absorption of these chiral drugs was nonstereoselective.…”
Section: Pharmacokinetics Of Chiral Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of binding results in up to twofold variations in free drugs in the plasma and the volume of distribution between the enantiomers. [29][30][31][32][33] For instance, many antiarrhythmic medicines that include disopyramide, encainide, flecainide, mexiletine, propafenone, and tocainide are marketed as racemates. The absorption of these chiral drugs was nonstereoselective.…”
Section: Pharmacokinetics Of Chiral Drugsmentioning
confidence: 99%
“…In the distribution context, most of the chiral drugs exhibit stereoselectivity for plasma protein binding. This type of binding results in up to twofold variations in free drugs in the plasma and the volume of distribution between the enantiomers 29–33 . For instance, many antiarrhythmic medicines that include disopyramide, encainide, flecainide, mexiletine, propafenone, and tocainide are marketed as racemates.…”
Section: Pharmacokinetics Of Chiral Drugsmentioning
confidence: 99%
“…Rarely, the determination of enantiomers of chiral drugs in biological samples was described. Flecainide, a chiral compound administered as a racemic mixture for the treatment of supraventricular tachyarrhythmias in human serum and urine was analyzed by HPLC-FLD [ 102 ]. The detection of flecainide by FLD does not require a pre-column derivatization process.…”
Section: Cardiovascular Drugsmentioning
confidence: 99%
“…In the last decade, four liquid chromatographic methods (Kristoffersen et al, 2007;Lee et al, 2010;Sørensen, 2012;Doki et al, 2014), one capillary electrophoretic method (Pietraś et al, 2007) and one Thin Layer Chromatographic (TLC) method (Pietraś and Kowalczuk, 2010) have been reported. Only one spectrofluorimetric method (Chang et al, 1983) and one electrochemical method (Stefan et al, 1997) were reported.…”
Section: Introductionmentioning
confidence: 98%